The Impact of Appropriateness of Empirical Antibiotic in Hospitalized Pneumonia Patients on Clinical Outcomes and Length of Stay - Syahrul Fath Thoriq; Nadia Farhanah Syafhan; Muhammad Luthfi Aziz (Eduvest - Journal of Universal Studies, 2024)
Pneumonia is the leading cause of morbidity and mortality in adults worldwide. The incidence of pneumonia is still very high in Indonesia. The main standard therapy for pneumonia is empirical antibiotic administration.  The purpose of this study was to determine whether there was an impact of the appropriateness of empirical antibiotics therapy on clinical outcomes and length of stay of non-ICU pneumonia patients at X Hospital in Jakarta. This study used a retrospective cohort design to determine the appropriateness of empirical antibiotics use in non-ICU pneumonia patients. The samples taken are all non-ICU pneumonia patients during the period January 2022 – December 2023 who met the inclusion criteria. Data analysis was carried out descriptively for patient characteristics, drug use profile, and the appropriateness of empirical antibiotic. A chi-square test was used to determine the impact of appropriateness of empirical antibiotics on clinical outcomes and length of stay. The appropriateness of empirical antibiotics obtained 59,5% (173 regimens) met category 0 (appropriate), and 40,5% (118 regimens) met category I-VI (inappropriate). Based on the results, there is an impact of the appropriateness of empirical antibiotics on clinical outcomes (P = 0,000; RR =1,916; 95% CI = 1,558 – 2,357), and impact of of the appropriateness of empirical antibiotics on length of stay (P = 0,002; RR =1,410; 95% CI = 1,126 – 1,765). The analysis's results showed that the impact of appropriateness of empirical antibiotic on clinical outcomes and length of stay of non-ICU inpatients with pneumonia at X Hospital in Jakarta.